HISTOIRE DE L'ETAT-NATION: DE LA POLITIQUE D'INTÉGRATION EN AMÉRIQUE LATINE ET EN EUROPE (Dialogos, 2018)
Resumo. O presente artigo trata de analisar as conseqÃ¼ências históricas, políticas, sociais e culturais da implantação do Estado-Nação como modelo político de Estado na Europa e na América Latina, tomando o caso do Peru como referência. Este modelo político de Estado, tanto na Europa quanto na América Latina, propõe o mito da nação como eixo unificador e centralizador da administração política. Esta unificação, oficial e arbitrária, não considera a existência real da diversidade cultural e lingÃ¼ística que na maioria dos casos impregna os territórios declarados pelo Estado como uma “!só nação”. Esta imposição autoritária se traduz em programas econômicos, políticos, educativos e culturais denominados de “integração nacional”, que não possibilitam a coexistência democrática da sociedade em sua pluralidade e multiculturalidade. Abstract. The present article attempts to analyze historical, political social and cultural the consequences of the implantation of the State-Nation as a State political model in Europe and Latin America, taking the Peruvian case as reference. This State political model, both in Europe and Latin America, proposes the myth of the nation as unifying and centralized axis of the political administration. This official and arbitrary unification, does not consider the real existence of the cultural and linguistic diversity, that in most of the cases impregnates to the territories declared by the State like a "single nation". This authoritarian imposition is crystallised into economic, political, educative and cultural programmes, called of "national integration", that do not make possible the democratic co-habitation of the society in its plurality and multi-cultural dimensions.